Crystal growth, experimental and theoretical studies on the electronic structure of CNGS and Nd:CNGS. Issue 19 (28th April 2016) - Ren, Junyu; Zhang, Xuzhao; Zhang, Xiaotong; Cheng, Rui; Guo, Jiayi; Zhang, Xiaoyang; Yu, Fapeng; Huang, Baibiao; Guo, Shiyi
Abstract : Ordered langasite single crystals CNGS and Nd:CNGS were grown using the Czochralski pulling technique. Experimental and theoretical studies on the electronic structure of the title crystals were performed. Abstract : Ca3 NbGa3 Si2 O14 (CNGS) and Nd:Ca3 NbGa3 Si2 O14 (Nd:CNGS) single crystals were grown using the Czochralski technique, and the dielectric, elastic and piezoelectric properties of the Nd:CNGS crystals were evaluated at room temperature by the impedance method. It is proved that the Nd:CNGS crystals have larger dielectric constants, piezoelectric constants and elastic compliance as compared with the CNGS crystals. The electronic structure and chemical composition of the crystals were analyzed using X-ray photoelectron spectroscopy (XPS). Constituent element representative core levels and auger lines in this complex langasite crystal have been measured. The Ca 2p, Ca 3p, Ga 3p, Ga 3d, Si 2p XPS spectra show a shift toward higher binding energies while the O 1s level moves in the lower binding energy direction with increasing Nd content and can be interpreted as a doping induced change in the chemical potential. Furthermore, it was confirmed by the X-ray photoelectron spectra that Ca–O, Ga–O, and Si–O bonds in Nd:CNGS have stronger ionicity compared with the CNGS crystal. On the basis of the density functional theory (DFT), first-principles calculations have been employed to study the electronic structure of CNGS successfully. The calculated results are essentially consistent with the corresponding experimental results, which indicate that the contributions of the Nb–O groups are dominant in the CNGS crystal for producing optical properties.